1988
DOI: 10.1002/jcp.1041340119
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tyrosinase levels in amelanotic and melanotic melanoma cell cultures by a competitive enzyme‐linked immunoadsorbent assay and by immunotitration analysis

Abstract: Melanogenesis in mammalian pigment cells is regulated by changes in the activity of tyrosinase, the rate-limiting enzyme for melanin synthesis. Because recent evidence suggests that this enzyme may exist in pigment cells in both active and inactive stages, a competitive enzyme-linked immunoadsorbent assay (ELISA) was developed to compare tyrosinase levels in amelanotic and melanotic melanoma cell clones. The melanotic cell line used for this study, MEL-11A, had basal tyrosinase levels approximately 40 times th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In addition, the expression of the products of the c and b loci are not dramatically increased in response to stimulation of differentiation (such as by MSH), although there are increases in the order of two-to threefold. These latter patterns, however, are in keeping with evidence that tyrosinase synthesis is in many ways constitutive, and that rapid and significant variations in melanogenic activity result more from activation of latent enzyme than from increases in enzyme synthesis [Fuller et al, 1987[Fuller et al, ,1988Jimenez et al, 1988;Wong and Pawelek, 19751. The sum ofthese studies emphasizes the importance of other ongoing work on the regulation of melanin production by post-tyrosinase factors, inhibitors, and other control mechanisms [Barber et al, 1984;Korner and Pawelek, 1980;Lamoreux et al, 1986;Pawelek et al, 19801. Thus the time has arrived for a critical reevaluation of all studies performed on the various pigment mutations at the biochemical, enzymatic level.…”
Section: Interaction Of Pigment-related Genessupporting
confidence: 60%
“…In addition, the expression of the products of the c and b loci are not dramatically increased in response to stimulation of differentiation (such as by MSH), although there are increases in the order of two-to threefold. These latter patterns, however, are in keeping with evidence that tyrosinase synthesis is in many ways constitutive, and that rapid and significant variations in melanogenic activity result more from activation of latent enzyme than from increases in enzyme synthesis [Fuller et al, 1987[Fuller et al, ,1988Jimenez et al, 1988;Wong and Pawelek, 19751. The sum ofthese studies emphasizes the importance of other ongoing work on the regulation of melanin production by post-tyrosinase factors, inhibitors, and other control mechanisms [Barber et al, 1984;Korner and Pawelek, 1980;Lamoreux et al, 1986;Pawelek et al, 19801. Thus the time has arrived for a critical reevaluation of all studies performed on the various pigment mutations at the biochemical, enzymatic level.…”
Section: Interaction Of Pigment-related Genessupporting
confidence: 60%
“…Similar conclusio~ its inhibitor is critical to the output of melanin bY the have been reached based on kinetic and immunologic melanocYte; e.g.9 in our studies On the effects Of the analyses of JBMS wearing et al, 1988; Jimenez et al, inhibitor on purified enzyme (Table 3) it can be seen that 1988), B16 and S91 (Pawelek, 1976; while only a slight inhibition of tyrosine hYdroxYlase Fuller et al, 1987Fuller et al, , 1988 melanoma cells, where in-activity occurs at the concentrations employed (10 to creases in the synthesis of tyrosinase and/or the adiva-30%'0), this has a profound effect on the produdion of tion of latent tyrosinase were insufficient to account for melanin in the same reaction mixture (50 to 70%). the dramatic increases in melanin Production elicited by MSH.…”
Section: )mentioning
confidence: 92%
“…Alpha-melanocyte stimulating hormone (a-MSH) is one such peptide hormone that has been suggested to modulate the pigment response. Studies have shown a role of a-MSH in promoting pigment synthesis (Fuller et al, 1987;Aroca et al, 1993). a-MSH binds to the melanocortin 1 receptor (MC1r), which is a member of the seventransmembrane receptor family that activates adenyl cyclase via G-protein signaling.…”
Section: Mitf As a Key Transcription Factor In The Pigment Biosynthesmentioning
confidence: 99%